Avoiding SARS-CoV-2 infection in healthcare workers: is behavioral change the answer? - Morales-Burton, Verónica; Lopez-Ramirez, Sofía A. (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic has become an important cause of morbimortality, and healthcare workers are at the highest risk of infection. As a result, policies and guidelines have been issued, and in hospitals, behavioral changes have been crucial. Among the measures, the implementation of personal protective elements (PPE) and their appropriate use in workplaces are key to avoiding contagion, as well as understanding the new measures regarding patient admission, distribution, and constant education in virtual platforms, among others, changing conduct to reduce contagion. However, behavioral change interventions in healthcare workers are challenging as contextual characteristics, attributes of the intervention, and psychological factors are involved. Study objectives: The problem elucidated is COVID-19 striking frontline emergency department healthcare workers at Fundación Cardioinfantil (FCI). The objective was to describe the behavioral change in emergency-department healthcare workers by studying and monitoring SARS-CoV-2 infection and their relationship through process tracing during 2020. Methods: We conducted a case study to identify and relate the SARS-CoV-2 infection rate within the personnel in the department, and healthcare workers’ response to the implementation and adherence to the use of PPE through the analysis of the different variables that contributed to behavioral change. Data were collected by a single author and analyzed by the two authors using both the individual-level logic model technique and triangulation of the information, with approval from the institutional review board. Discussion: Several interventions for behavior change were registered in the data collection process. Implementation, embedding, and integration as collective and individual behavior processes were perceived in the data obtained, with evidence on healthcare interventions: education, incentivization, training, restriction, environmental restructuring, modeling, and enablement. Conclusion: Behavioral science should be part of public health responses, as the theoretical base suggests change may enhance the answer to avoid infectious diseases' transmission. Therefore, individuals at the highest risk appear to adopt guidance with targeted behavior adaptation interventions. Efforts to inform, instruct, and motivate healthcare workers must be continuous, and actions at the community level strengthened, as it is human behavior which determines the spread and mortality of infectious diseases, where community compliance with prevention behavior plays a crucial role.